Prevalence of temporomandibular dysfunction and pain syndrome and associated factors in dental students - Martínez, Luisa; Mendivelso, Cindy; Bustamante, Paula; Sánchez, César; Sarrazola, Ángela (Revista Estomatología, 2015)
Background: Temporomandibular joint dysfunction and pain syndrome (TMJD) has been identified as one of the principle causes of non-dental pain in the orofacial region. Objective: To describe the prevalence of TMJD and associated factors in the students of the faculty of odontology of the University Cooperativa de Colombia (UCC), Envigado campus. Materials and methods: Observational, descriptive and cross-sectional study. 98 randomly selected students were evaluated. A survey, clinical examination, Helkimo index, emotional distress and anxiety test was performed. Univariate and bivariate analysis was performed (Chi2, p